2014
DOI: 10.1098/rsbl.2014.0134
|View full text |Cite
|
Sign up to set email alerts
|

Fenestration: a window of opportunity for carnivorous plants

Abstract: A long-standing but controversial hypothesis assumes that carnivorous plants employ aggressive mimicry to increase their prey capture success. A possible mechanism is that pitcher plants use aggressive mimicry to deceive prey about the location of the pitcher's exit. Specifically, species from unrelated families sport fenestration, i.e. transparent windows on the upper surfaces of pitchers which might function to mimic the exit of the pitcher. This hypothesis has not been evaluated against alternative hypothes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 9 publications
1
10
0
Order By: Relevance
“…The low capture probability of Darlingtonia was later estimated to be approximately 1.7% of vespulid wasps that had already landed on a pitcher leaf (Dixon et al, 2005). The probability of successful prey capture (compared with the overall number of visits) in other pitcher plant species is similarly low, and experimental and observational studies have failed to support the hypothesized roles of numerous other foliar traits in prey capture (Cresswell, 1993; Green and Horner, 2007; Bennett and Ellison, 2009; Schaefer and Ruxton, 2014). These findings, along with the common observation of insects feeding on pitcher leaves and avoiding capture, beg an alternative explanation for the fishtail appendage's role.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The low capture probability of Darlingtonia was later estimated to be approximately 1.7% of vespulid wasps that had already landed on a pitcher leaf (Dixon et al, 2005). The probability of successful prey capture (compared with the overall number of visits) in other pitcher plant species is similarly low, and experimental and observational studies have failed to support the hypothesized roles of numerous other foliar traits in prey capture (Cresswell, 1993; Green and Horner, 2007; Bennett and Ellison, 2009; Schaefer and Ruxton, 2014). These findings, along with the common observation of insects feeding on pitcher leaves and avoiding capture, beg an alternative explanation for the fishtail appendage's role.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, certain morphological characters of Nepenthes (Nepenthaceae) pitcher organs have been shown to serve mutualistic, rather than predatory, roles with arthropods and mammals (Clarke et al, 2010; Grafe et al, 2011; Bazile et al, 2012). Likewise, many leaf traits hypothesized to facilitate prey capture in Sarracenia (Sarraceniaceae) serve either an alternative or no detectable function upon empirical evaluation (Cresswell, 1993; Green and Horner, 2007; Bennett and Ellison, 2009; Schaefer and Ruxton, 2014).…”
mentioning
confidence: 99%
“…Moran et al 37 found that in the pitcher plant species Nepenthes aristolochioides, the light coming through the translucent pitcher windows causes a visual illusion of false exits, helping to keep the prey inside the trap. However, Schaefer and Ruxton 38 found that the windows in the species Sarracenia minor do not serve as false exits but rather function in long-range visual attraction of prey. (2) "Windows in traps aimed for pollination that cause pollinating trapped insects to stay longer within the trap.…”
Section: Resultsmentioning
confidence: 99%
“…Plant-animal communication via transparent tissues was considered in 2 plant types: (1) For pitcher carnivorous plants, 37,38 although via 2 different mechanisms, demonstrating that illumination through transparent plant tissues can be used in more than one way. Moran et al 37 found that in the pitcher plant species Nepenthes aristolochioides, the light coming through the translucent pitcher windows causes a visual illusion of false exits, helping to keep the prey inside the trap.…”
Section: Resultsmentioning
confidence: 99%
“…(as pointed out by Jebb 1991), and Sarracenia psittacina Michx. (Schaefer & Ruxton 2014). In laboratory conditions Moran et al (2012) showed with N. aristolochioides that flies of Drosophila melanogaster arriving under the opaque lid, which shades the mouth, land on the vertically held peristome, feed on the nectar, and depart towards the light window at the rear and top of the pitcher, becoming stuck to the non-waxy wall and due to the viscid fluid slowly slide down towards the base where digestion occurs.…”
Section: Nepenthes Madagascariensismentioning
confidence: 99%